Luminescence properties of CsI:Tl crystals codoped with Eu - Nagarkar, V.V.; Ovechkina, E.E.; Miller, S.R.; Gaysinskiy, V.; Brecherb, C.; Lempickib, A.; Bartramc, R.H. (Functional Materials, 2005)
In investigating chemical approach for reducing the afterglow from Csl:TI, we were discovered es that a particularly effective ion for such afterglow suppression is Eu²⁺. We have extensively studied the effect of the Eu codopant on the luminescence from crystals of Csl:TI. Numerous single crystals of Csl:TI,Eu were grown by the Bridgman technique in evacuated quartz ampoules at concentrations between 0.05 and 0.5 mole percent. Three different materials were investigated as sources for the codopant: two variants of Eul₂ and elemental Eu metal. X-ray excited spectra revealed the presence of an additional peak at about 460 nm, characteristic of Eu²⁺ ions in the Csl lattice. The decay traces of the specimens reveal substantial variation in afterglow suppression, and possible reasons for these differences are examined and discussed.